2018
DOI: 10.1002/clc.23065
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate: A prognostic marker in atrial fibrillation—A subanalysis of the AntiThrombotic Agents Atrial Fibrillation

Abstract: The result of this post-hoc analysis indicates that an impaired eGFR is independently associated with worse prognosis among patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While many authors detected a higher proportion of men in AF patients with CKD, Prioetti et al and Reinecke et al reported a higher proportion of women than men in AF patients with CKD. [ 26 , 33 ] We failed to find a difference in gender proportion between CKD and non-CKD patients. Reinecke et al speculated whether a higher proportion of women could be a reflection of previous higher mortality in men.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While many authors detected a higher proportion of men in AF patients with CKD, Prioetti et al and Reinecke et al reported a higher proportion of women than men in AF patients with CKD. [ 26 , 33 ] We failed to find a difference in gender proportion between CKD and non-CKD patients. Reinecke et al speculated whether a higher proportion of women could be a reflection of previous higher mortality in men.…”
Section: Discussionmentioning
confidence: 85%
“…In the linear regression analysis, CV mortality was independently associated with eGFR (β= 0.169, P = .04) what is in line with the results of Parsons et al [ 31 ] who found that lower GFR significantly correlated with mortality and following data of Proietti et al where eGFR < 60 ml/min/1.73 m 2 was associated with higher CV mortality rate. [ 26 ] It was observed in J Rhythm and ATA-AF registries that even moderately impaired GFR was independently associated with CV mortality and worse prognosis among patients with AF while Guo et al reported that renal dysfunction carries a greater risk of stroke and death in women. [ 32 , 36 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with some other AF registry studies; Boriani et al ( 2016 ) assessed 1‐year outcomes in patients with AF enrolled in the EurObservational Research Programme AF General Pilot Registry, they enrolled 2398 AF patients and found that renal function was a major determinant of adverse outcomes at 1 year, and even mild or moderate renal impairments were associated with an increased risk of all‐cause death (OR 3.64 for estimated glomerular filtration rate (eGFR) < 30 ml/min/1.73 m 2 , OR 3.30 for 30–49 ml/min/1.73m 2 , and OR 2.09 for 50–79 ml/min/1.73 m 2 vs. eGFR≥80 ml/min/1.73 m 2 ). Proietti et al (Proietti et al, 2018 ) performed on the data of the Antithrombotic Agents Atrial Fibrillation study and showed that impaired eGFR ( < 60 ml/min/1.73 m 2 ) heralds a higher risk for cardiovascular morbidity and all‐cause mortality among patients with AF. In the Fushimi AF Registry study (Abe et al, 2017 ), AF Patients with CrCl < 30 ml/min had the greatest risk s of all‐cause death, stroke, major bleeding, and hospitalization for myocardial infarction and HF.…”
Section: Discussionmentioning
confidence: 99%
“…eGFR≥80 ml/min/1.73 m 2 ). Proietti et al (Proietti et al, 2018) performed on the data of the Antithrombotic Agents Atrial Fibrillation study and showed that impaired eGFR ( < 60 ml/min/1.73 m 2 ) heralds a higher risk for cardiovascular morbidity and all-cause mortality among patients with AF. In the Fushimi AF Registry study (Abe et al, 2017), AF Patients with CrCl < 30 ml/min had the greatest risk s of all-cause death, stroke, major bleeding, and hospitalization for myocardial infarction and HF.…”
Section: Renal Impairment and Deathmentioning
confidence: 99%
“…Once appeared, AF favors CKD progression resulting in a vicious cycle [ 4 , 5 ]. Thromboembolic complications typical of AF are amplified in patients with renal dysfunction, who may have a hypercoagulable state due to increased platelet activity, activation of the renin-angiotensin-aldosterone system, altered vessel wall contractility and vascular endothelium changes, increasing the risk of stroke by 50% [ 4 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%